Pemanfaatan Buah dan Sayur Sebagai Upaya Antisipasi Konstipasi pada Anak di TK Mekar Siwi Panjen Maguwoharjo, Depok, Sleman - Widiany, Fery Lusviana; Prasetyaningrum, Yunita Indah; Afriani, Yuni (Jurnal Pengabdian Dharma Bakti, 2020)
Good nutrition in childhood is important, not only for health, growth and development of children but also for long-term health. Children need to eat a variety of nutrient-rich foods regularly, including fruits and vegetables. Lack of consumption of fruit and vegetables can increase the likelihood of constipation. A strategy is needed to support the development of children in the selection of variations of fruits and vegetables consumed, which can be done through nutrition counseling efforts in children especially children in kindergarten (kindergarten). In addition, modification of food based on fruits and vegetables is needed to improve children's appetite, so as to increase fiber intake in children in an effort to prevent constipation.Keywords: Children; Fruit; Constipation; Dietary habit; Vegetables.